Nine Localized Deviations from Keplerian Rotation in the DSHARP Circumstellar Disks: Kinematic Evidence for Protoplanets Carving the Gaps - Pinte, C.; Price, D. J.; Ménard, F.; Duchêne, G.; Christiaens, V.; Andrews, S. M.; Huang, J.; Hill, T.; van der Plas, G.; Perez, L. M.; Isella, A.; Boehler, Y.; et al. (Astrophysical journal. Letters, 2020)
We present evidence for localized deviations from Keplerian rotation, i.e., velocity "kinks," in 8 of the 18 circumstellar disks observed by the DSHARP program: DoAr 25, Elias 2-27, GW Lup, HD 143006, HD 163296, IM Lup, Sz 129, and WaOph 6. Most of the kinks are detected over a small range in both radial extent and velocity, suggesting a planetary origin, but for some of them foreground contamination prevents us from measuring their spatial and velocity extent. Because of the DSHARP limited spectral resolution and signal to noise in the 12CO J = 2−1 line, as well as cloud contamination, the kinks are usually detected in only one spectral channel, and will require confirmation. The strongest circumstantial evidence for protoplanets in the absence of higher spectral resolution data and additional tracers is that, upon deprojection, we find that all of the candidate planets lie within a gap and/or at the end of a spiral detected in dust continuum emission. This suggests that a significant fraction of the dust gaps and spirals observed by Atacama Large Millimeter/submillimeter Array in disks are caused by embedded protoplanets.